Experimental study of heat transfer enhancement using nanofluid in double tube heat exchanger. (December 2017) - Han, D.; He, W.F.; Asif, F.Z.
Abstract: This study aims at experimentally investigating the effect of Al2 O3 /water nanofluids on the heat transfer enhancement inside the double tube heat exchanger at variable inlet temperature. Al2 O3 nanoparticle with concentration of 0.25% and 0.5% by volume concentration has been used at different inlet temperature. The experimental setup consisted of double tube heat exchanger with nanofluids on the cold side was used in turbulent regime with Reynolds number ranging from 20000 to 60000. Results from the study shows that the heat transfer increases with the increase in temperature and volume concentration of nano-particles. Significant improvement over the water is seen with maximum Nusselt number increase up to 24.5% at 50℃ inlet temperature.